Our Experience of Perinatal Outcomes in Pre-Eclampsia and Eclampsia Cases: A Clinical Study at a Tertiary Khairpur Medical College Hospital (KMCH) Sindh (Medical Forum Monthly, 2024)
Objective: To evaluate the perinatal outcomes in pre-eclampsia and eclampsia cases and to investigate their association with the socio-demographic status of women at the Tertiary care hospital of Khairpur Medical College Hospital of Sindh.Study Design: This hospital-based observational study.Place and Duration of Study: This study was conducted at the Gynaecology Ward and Nursery of Khairpur Medical College Hospital (KMCH), Sindh, from July 2023 to June 2024.Methods: In this study investigated the perinatal outcomes in cases of pre-eclampsia and eclampsia. Data was collected through patient interviews and neonatal assessments. Key maternal parameters recorded included age, parity, and gestational age at diagnosis. Neonatal outcomes were assessed based on birth weight, stillbirths, low birth weight, and intrauterine death.Results: A total of 308 women who met the inclusion criteria were included in this study. The mean age of the women was 28.32±5.87 years. These 308 women gave live birth to 172 (55.8%) babies, and (40.3%) had stillbirths, whereas 12 (3.9%) had IUDs. The majority of live births (83, 48.3%) had a birth weight greater than 2.5 kg, whereas most stillbirths (69, 55.6%) and IUDs (5, 41.7%) had a birth weight between 2 and 2.5 kg.Conclusion: Pre-eclampsia and eclampsia remain major problems in developing countries. They cause significant perinatal complications. Lack of education and awareness worsens outcomes, especially in low socio-economic groups. Perinatal mortality rates remain high. Expanding medical services to rural areas is crucial for better perinatal care.